Patient Satisfaction on Hospital Outpatient Service Quality Based on the Donabedian Model - Setyaningrum, Dian; Sriatmi, Ayun; Arso, Septo Pawelas (Journal of Public Health for Tropical and Coastal Region, 2024)
Introduction: The Community Satisfaction Index at BS Hospital in 2021 and 2022 were low, with an average of 86.92 and 89.73, respectively. This levels was lower than the standard set of at least ≥ 90% by the Minister of Health Decree of number 129/ Menkes/ SK/ II/ 2008. This study aimed to determine the description of patient satisfaction with the quality of outpatient services.Methods: This study is a quantitative study with a descriptive approach and data collection using interview techniques on 134 subjects who were outpatients and non-patients who were the families or members of hospital employees. This study used Donabedian theory with a structure, process, and outcome approach. Data collection were done through interviews using structured questionnaires. Data analysis were conductedResults: The study results showed that the lowest satisfaction was attributed to the structure (hospital facilities) in parking services (76%), the process of doctor services (87%) and nurse services (90%).Conclusion: Overall, patients’ satisfaction to the quality of the structure, process, and the results at the Outpatient Installation were less than the minimum service standards of the Hospital according to the Ministry of Health. Actions should be taken to improve the parking facilities